Differentiated characteristics, sustainability performance and preferences among small-scale aquaculture producers: implications for sustainable intensification - Brako Dompreh, Eric; Wang, Quanli; Su, Jie; Dam Lam, Rodolfo; Barman, Benoy; Rossignoli, Cristiano; Gasparatos, Alexandros (Springer, 2025)
Inland aquaculture is becoming an important source of animal-based protein in many low- and middle-income countries of Asia. In several of these countries such as Bangladesh the inland aquaculture sector is dominated by small-scale producers that rely on unimproved production practices. However, the heterogeneity of these producers is not well understood, leading to assumptions of low variability in both the underlying characteristics of aquaculture production systems, as well as their sustainability performance. This in turn can lead to the ineffective design and implementation of interventions and policies for the sustainable intensification of the sector. This study explores the differentiated characteristics, sustainability performance and preferences among carp producers in Bangladesh. We focus on Bangladesh as it is the 5th largest inland aquaculture producer globally, with the sector contributing significantly to livelihoods and food security. We undertake comprehensive in person surveys with 4540 carp producers across 54 regions of the country. We use 18 production variables to develop a nuanced typology of carp production systems using Principal Component Analysis (PCA) and Hierarchical Clustering Approach (HCA). We then assess whether these production systems have significantly different sustainability performance across eight socioeconomic and environmental indicators. Finally, we elicit the preferences of producers for improved carp species through three choice experiments. Overall, we identify four major types of carp production systems, characterized by very different production characteristics, sustainability performance and preferences for improved fish species attributes. Collectively, our results provide a nuanced picture of the carp aquaculture sector in Bangladesh, which moves beyond simple binaries (e.g., commercial vs. subsistence; intensive vs. extensive; large-scale vs. small-scale). This information can inform the development and implementation of fit-for-purpose interventions for the sustainable intensification of the sector.